Preparation and characterization of calcium silicate for CO2 sorption - Kale, Kishor B.; Raskar, Reshma Y.; Rane, Vilash H.; Gaikwad, Abaji G. (Adsorption Science & Technology, 2012)
An attempt has been made to develop different samples of calcium silicate and to screen these samples for CO2 sorption and alkalinity in order to achieve maximum CO2 sorption. The CO2 sorption capacity of these samples was examined at different temperatures. Various methods such as solid-solid fusion, sol-gel, molten salt and templates (CTAB, cetyltrimethylammonium bromide or Aliquat 336, tricaprylmethylammonium chloride) were used to prepare the calcium silicate samples. The solid mass of calcium silicate samples were obtained by calcining the solid product obtained in an atmosphere of air or helium at 900 degrees C for 3 hours. The calcium silicate samples were characterized for surface area, alkalinity, scanning electron microscopic images and X-ray diffraction patterns. The temperature profile of CO2 sorption by calcium silicate was studied in the temperature range of 40-850 degrees C. Our results showed that the alkalinity and surface area of calcium silicate were in the range from 2.35 to 20 mmol g(-1) and 1.4 to 10 m(2) g(-1), respectively. The sorption of CO2 at 500 degrees C over calcium silicate for the different Ca/Si mol ratio (range: 1-6) was found to be in the range from 3.12 to 29.96 wt%. Addition of a promoter such as sodium, potassium, caesium and lanthanum was found to enhance the sorption of CO2 by calcium silicate. Several samples of different mol ratios of Ca/Si prepared by different methods were tested for the sorption of CO2 at 500 degrees C.